2017
DOI: 10.1161/jaha.116.004892
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Heart Failure Readmitted to the Original Hospital Have Better Outcomes Than Those Readmitted Elsewhere

Abstract: BackgroundUp to one fifth of readmissions after a heart failure hospitalization occur at a different hospital. This negatively impacts information continuity, but whether site of readmission impacts subsequent outcomes is unclear.Methods and ResultsRetrospective cohort study of all patients discharged with a primary diagnosis of heart failure in Canada between April 2004 and December 2013. We compared patients readmitted within 30 days to the original hospital versus a different hospital. Of the 217 039 heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…This suggests that addressing care fragmentation in gastroparesis could reduce healthcare costs but does not change the natural history or morbidity of the disease. Other studies conducted on patients with heart failure and other critical illnesses found higher mortality in patients admitted to a non-index hospital[ 12 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that addressing care fragmentation in gastroparesis could reduce healthcare costs but does not change the natural history or morbidity of the disease. Other studies conducted on patients with heart failure and other critical illnesses found higher mortality in patients admitted to a non-index hospital[ 12 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 The dataset of the present study was limited to a population of patients admitted under medical teams for the index admission. This is unlikely to be the reason for the lack of a difference in inpatient mortality, because a North American study of heart failure patients, 13 also presumably admitted under medical teams, reported not only a greater risk of in-patient death during non-index admissions, but also a longer LOS compared with index-admitted counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…12 Other studies confirmed the greater LOS and a higher 30-day mortality, and found higher costs with non-index hospital readmissions. 2,3,13 These adverse consequences could be due to inadequate exchange of health information, inaccurate medication reconciliation and lack of coordination across sites of care. 12,14 The corresponding situation in Australia has not yet been studied thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 3 Available empirical evidence shows that the great majority (on average, around 85%-90%) of patients needing readmission are readmitted to the same hospital where they received the first treatment (see, e.g., Staples et al, 2014;Tsai et al, 2015;McAlister et al, 2017). 7 In what follows, we characterise the Nash equilibrium, assuming an open-loopinformation structure.…”
Section: Modelmentioning
confidence: 99%
“…Under this information structure, players choose the optimal plan at the beginning of the game, knowing the initial state of the system (i.e., D(0) = D 0 ), and then stick to it forever (i.e., q OL i = (t)). Then, 3 Available empirical evidence shows that the great majority (on average, around 85%-90%) of patients needing readmission are readmitted to the same hospital where they received the first treatment (see, e.g., Staples et al, 2014;Tsai et al, 2015;McAlister et al, 2017). Therefore, for the sake of simplicity, readmission here is intended as the readmission to the same hospital.…”
Section: Modelmentioning
confidence: 99%